An adaptive PAM-4 5-Gb - Stonick, J.T.
This paper describes a backplane transceiver, which uses pulse amplitude modulated four-level (PAM-4) signaling and continuously adaptive transmit-based equalization to move 2.5-GBd/s symbols totalling 5 Gb/s across typical FR-4 backplanes for total distances of up to 50 inches through two sets of backplane connectors. The 17-mm2 device is implemented in a 0.25-μm CMOS process, operates off of 2.5- and 3.3-V supply voltages, and consumes 1 W.
Keywords: 0.25 micron; 1 W; 2.5 V; 3.3 V; 5 Gbit/s.; CMOS process; PAM-4.; Adaptive equalization; Backplane transceiver; Four-level signaling; Pulse amplitude modulation